DİFFİCULTİES OF LEARNİNG GERMAN AS A FOREİGN LANGUAGE İN A NON-LİNGUİSTİC ENVİRONMENT: LİNGUİSTİC AND CULTURAL BARRİERS - Allahverdiyeva, A.B.; Yusifli, A.N. (SWorldJournal, 2025)
The article analyzes the main linguistic and cultural barriers that arise when teaching German as a foreign language in the absence of a natural language environment. Typical errors related to interference of the native language, literal translation and i